Measurement of the polarisation of W bosons produced with large transverse momentum in pp collisions at √s =7 TeV with the ATLAS experiment - Anduaga, Xabier Sebastián (2012)
This paper describes an analysis of the angular distribution of W → eν and W → μν decays, using data from pp collisions at √ s = 7 TeV recorded with the ATLAS detector at the LHC in 2010, corresponding to an integrated luminosity of about 35 pb−1. Using the decay lepton transverse momentum and the missing transverse momentum, the W decay angular distribution projected onto the transverse plane is obtained and analysed in terms of helicity fractions f0, fL and fR over two ranges of W transverse momentum (pW T ) : 35<pW T < 50 GeV and pW T > 50 GeV. Good agreement is found with theoretical predictions. For pW T > 50 GeV, the values of f0 and fL − fR, averaged over charge and lepton flavour, are measured to be: f0 = 0.127±0.030±0.108 and fL−fR = 0.252±0.017±0.030, where the first uncertainties are statistical, and the second include all systematic effects.